2014
DOI: 10.1002/lary.24882
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric tracheostomy revisited: A nine‐year experience using horizontal intercartilaginous incision

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…Tracheostomy complications occur surprisingly frequently and influence outcomes . One recent North American paediatric tertiary centre study reported early complications in 11% and late complications in 68.8% of all tracheostomies inserted , which is consistent with other reported institutional case series . The early postoperative complication rate in preterm infants may be double that of full‐term infants , and the requirement for tracheostomy in the preterm period is also associated with poor developmental outcomes .…”
Section: Introductionsupporting
confidence: 79%
“…Tracheostomy complications occur surprisingly frequently and influence outcomes . One recent North American paediatric tertiary centre study reported early complications in 11% and late complications in 68.8% of all tracheostomies inserted , which is consistent with other reported institutional case series . The early postoperative complication rate in preterm infants may be double that of full‐term infants , and the requirement for tracheostomy in the preterm period is also associated with poor developmental outcomes .…”
Section: Introductionsupporting
confidence: 79%
“…The effect of the type of tracheal incision on the subsequent stenosis and tracheomalacia rate in children has been a subject of considerable discussion, with various operative techniques being advocated to minimize the risk and complications. 58,[61][62][63] There are 3 main concerns that should be reviewed when a tracheostomy incision site is being considered: prevention of accidental decannulation (this is the primary cause of tracheostomyrelated fatality in children); prevention of long-term tracheal stenosis 58,64 ; and awareness of the underlying indication for tracheostomy. For example, if the child has subglottic stenosis that will be repaired as a single-stage procedure in the future, it may be beneficial to place the tracheostomy high in the neck.…”
Section: Surgical Tracheostomymentioning
confidence: 99%
“…47 There is an ongoing debate as to whether a vertical or horizontal tracheal incision, with or without flap, should be made. [62][63][64][65] The basic principle consists of incising as few tracheal rings as possible. Irrespective of the incision used, the tube is likely to inflict some damage on the tracheal cartilage.…”
Section: Surgical Tracheostomymentioning
confidence: 99%
“…20,22 Bununla birlikte Song ve ark., horizontal trakeal insizyon ile açtıkları 111 pediatrik trakeotomi hastasında, komplikasyon ve mortalite oranlarının literatürle uyumlu olduğunu belirtmişlerdir. 23 Trakeotomi sonrası erken dönemde karşılaşılan ve mortaliteye sebep olabilen önemli bir sorun da kazara dekanülasyondur. 24,25 Tüpün tekrar yerleştirilmesi sırasında trakea ön yüzünden anterior mediastene uzanan bir false pasaj oluşması riski ve buna bağlı hastanın havalandırılamaması erken dekanülasyonu tehlikeli bir durum kılmaktadır.…”
Section: Preoperati̇f Değerlendi̇rme Ve Cerrahi̇ Tekni̇kunclassified